Synergies between China's whole county PV program and rural heating electrification - Anders Hove (The Oxford Institute for Energy Studies, 2023)
Electrification of heating, particularly with highly efficient heat pumps, is increasingly viewed as essential for reaching the targets of the Paris Climate Agreement. In China, rural heating has long represented a major contributor to local air pollution, poor indoor air quality, and significant greenhouse gas emissions from coal burning. For years China has promoted replacement of dirty coal heating in rural areas, initially with natural gas, and more recently with clean coal stoves, both of which have significant emissions. More recently China has also begun promoting distributed solar PV as a rural development strategy, particularly with the launch of the Whole County PV pilots in 2021. The Whole County PV pilot program centres on having at least a minimum percentage of rooftops equipped with solar PV-20 per cent in the case of residential rooftops. Several analyses have shown that heat pumps are economical in China, including when paired with solar PV. However, the Whole County PV program has not been specifically studied. This study suggests that expanding the Whole County PV program to incorporate energy efficiency and heating/cooling measures could represent an economically attractive way to accelerate the rural energy transition and improve rural livelihoods. Barriers to such an approach include involvement of different government ministries, the cost of upgrading building insulation, the design of building codes, and the structure of electricity tariffs. While these barriers are significant, they also represent some of the same barriers that previously hindered distributed PV adoption, suggesting that the design of the Whole County PV program might be applied to help address these barriers. From a wider perspective, residential heating and cooling represent a relatively straightforward way to abate carbon emissions, given that an economically attractive and technically viable technology already exists. Scaling up heat pump adoption in rural areas would also greatly expand manufacturing of heat pumps in China, with the potential to boost availability of low-cost heat pumps for adoption of this technology worldwide.
Keywords: 330; China; China energy; heat-pumps; Heating; solar PV